Decreased adiponectin level in adults with central obesity and low 25-hydroxy vitamin D level - Pusparini, Pusparini; Merijanti, Lie Tanu; Lesmana, Alvina; Meiyanti, Meiyanti (Universa Medicina, 2017)
Background Vitamin D insufficiency is associated with obesity and central obesity, which is in turn associated with the accumulation of visceral fat. Visceral fat secretes adiponectin which has a role in the pathogenesis of the metabolic syndrome, diabetes mellitus and cerebrovascular disease. The aim of this study was to determine the relationship between serum 25-hydroxy vitamin D [25(OH)D] level and adiponectin level in adults with central obesity. Methods This study was a cross sectional study with 80 subjects with central obesity and 80 healthy subjects as controls. The age of the subjects ranged from 55 to 65 years. The data collection included anthropometry and blood biochemistry (lipid profile, fasting blood glucose, 25(OH)D, and adiponectin). The data were analyzed using independent t test with p <0.05.Results Mean waist circumference and 25(OH)D level in the central obesity group were 94.9 ± 7.8 cm and 14.3 ± 6.6 ng/mL, respectively, and in the control group 72.4 ± 5.0 cm and 19.2 ± 8.6 ng/mL respectively. There were significant differences in adiponectin level between the central obesity group and the control group at the 25(OH)D level of <20 ng/mL (p=0.001), but no significant differences between the two groups at the 25(OH)D level of ³20 ng/mL (p=0.538).Conclusion The central obesity subgroup with 25(OH)D level of <20 ng/mL have lower adiponectin levels compared with the control group. This study demonstrates the role of adiponectin as a link between insulin resistance and vitamin D status in adults.